2012
DOI: 10.5534/wjmh.2012.30.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic-Induced Sexual Dysfunction and Its Management

Abstract: Sexual dysfunction is a common condition in patients taking antipsychotics, and is the most bothersome symptom and adverse drug effect, resulting in a negative effect on treatment compliance. It is known that hyperprolactinemia is a major cause of sexual dysfunction. Based on the blockade of dopamine D2 receptors, haloperidol, risperidone, and amisulpride are classed as prolactin-elevating antipsychotics, while olanzapine, clozapine, quetiapine, ziprasidone, and aripiprazole are classed as prolactin-sparing dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 42 publications
0
45
0
2
Order By: Relevance
“…In addition, APs may cause other sexual side effects such as erectile dysfunction, delayed orgasm and impaired lubrication (138Á140). Sexual side effects are most prevalent in those APs that have the most pronounced D2 antagonism, mainly typical APs and risperidone (141). One study suggests that erectile dysfunction and other sexual dysfunctions in men, as a side effect of AP treatment, is linked to a polymorphism of the dopamine D2 receptor ((141C Ins/Del [rs179973]) (142).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…In addition, APs may cause other sexual side effects such as erectile dysfunction, delayed orgasm and impaired lubrication (138Á140). Sexual side effects are most prevalent in those APs that have the most pronounced D2 antagonism, mainly typical APs and risperidone (141). One study suggests that erectile dysfunction and other sexual dysfunctions in men, as a side effect of AP treatment, is linked to a polymorphism of the dopamine D2 receptor ((141C Ins/Del [rs179973]) (142).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…On the basis of the blockade of dopamine D2 receptors, a study conducted by Park et al [4] classed haloperidol, risperidone, and amisulpride as prolactin-elevating antipsychotics, whereas olanzapine, clozapine, quetiapine, ziprasidone, and aripiprazole were classed as prolactinsparing drugs. They found that risperidone and the other typical antipsychotics are associated with a high rate of sexual dysfunction compared with olanzapine, clozapine, quetiapine, and aripiprazole.…”
Section: Discussionmentioning
confidence: 98%
“…The rate of incidence of sexual dysfunction has been estimated to be 31% in the general population and 60% in patients with schizophrenia treated with antipsychotics [1,2]. It is highly prevalent in both treated and untreated schizophrenic patients, affecting 30-80% of woman and 45-80% of men [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of hyperprolactinaemia are different in men and women 6. Men are likely to experience loss of libido and erectile dysfunction 7. Women are more likely to develop oligomenorrhoea and amenorrhoea.…”
Section: Introductionmentioning
confidence: 99%